PENGOLAHAN DATA MIKROTREMOR BERDASARKAN METODE HVSR DENGAN MENGGUNAKAN MATLAB - Winda Styani Yuliawati; Syamsurijal Rasimeng; Karyanto Karyanto (Engineering Faculty Universitas Lampung, 2019)
The research has conducted to get the result of Matlab program for microtremor data processing. The purpose of this research is to apply Matlab software into microtremor data processing. The microtremor is the ground motion to identify earthquake vulnerability by using HVSR (Horizontal to Vertical Spectral Ratio) method. The HVSR method for comparing both of horizontal component and vertical component on microtremor wave to obtain the result dominant frequency(f0) based on the high spectrum H/V value from the analysis of HVSR curve. Based on this research which concludes that microtremor data processing has processed using Matlab software. The result of this data processing gives similar value from the geopsy software. The value of dominant frequency by Matlab software and geopsy software calculation are classified on the site class type II which is dominantly alluvium. Whereas, the result of dominant period by geopsy and Matlab are classified on the site class type I which shows as the bedrock.